A Modular Approach and Simulation of an Asynchronous Machine - Zineb Mekrini; Seddik Bri (Institute of Advanced Engineering and Science, 2016)
This article presents the modeling and simulation of the asynchronous machine. The aim of this research is the mastery of the electrical, mechanical and magnetic behaviors of this type of machine. The Matlab/Simulink is used for simulation two types of no-load and additional load services in transitional and permanent operation. The Analytical equations describing the two operating systems are evaluated and developed by a generalized model of a three-phase induction motor. The simulation results presented in this article confirms that the proposed model gave a satisfactory response in terms of torque characteristics and speed.